Open-Shell Nonbenzenoid Nanographenes Containing Two Pairs of Pentagonal and Heptagonal Rings - Liu, Junzhi; Mishra, Shantanu; Pignedoli, Carlo A; Passerone, Daniele; Urgel, José I; Fabrizio, Alberto; Lohr, Thorsten G; Ma, Ji; Komber, Hartmut; Baumgarten, Martin; Corminboeuf, Clémence; Berger, Reinhard; et al. (Journal of the American Chemical Society, 2019)
Nonbenzenoid carbocyclic rings are postulated to serve as important structural elements toward tuning the chemical and electronic properties of extended polycyclic aromatic hydrocarbons (PAHs, or namely nanographenes), necessitating a rational and atomically precise synthetic approach toward their fabrication. Here, using a combined bottom-up in-solution and on-surface synthetic approach, we report the synthesis of nonbenzenoid open-shell nanographenes containing two pairs of embedded pentagonal and heptagonal rings. Extensive characterization of the resultant nanographene in solution shows a low optical gap, and an open-shell singlet ground state with a low singlet–triplet gap. Employing ultra-high-resolution scanning tunneling microscopy and spectroscopy, we conduct atomic-scale structural and electronic studies on a cyclopenta-fused derivative on a Au(111) surface. The resultant five to seven rings embedded nanographene displays an extremely narrow energy gap of 0.27 eV and exhibits a pronounced open-shell biradical character close to 1 (y 0 = 0.92). Our experimental results are supported by mean-field and multiconfigurational quantum chemical calculations. Access to large nanographenes with a combination of nonbenzenoid topologies and open-shell character should have wide implications in harnessing new functionalities toward the realization of future organic electronic and spintronic devices.